2015
DOI: 10.1200/jop.2014.001495
|View full text |Cite
|
Sign up to set email alerts
|

Financial Burden of Pediatric Cancer for Patients and Their Families

Abstract: Efforts to reduce unexpected hospitalizations and employment disruptions by providing more comprehensive supportive care for pediatric patients with cancer could help ease families' financial burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 23 publications
5
101
1
2
Order By: Relevance
“…An analysis of written responses, provided by the 21.2% of survivors who reported that their caregivers made “other” work changes, revealed that caregivers made a broad array of changes to their schedules, job responsibilities and in some cases their careers in order to transport the survivor to and from their medical appointments and provide care during recovery. These findings are consistent with previous research reporting that cancer caregivers miss work, work fewer hours, or make career changes as a result of their caregiving responsibilities [13, 12, 14, 24, 15]. Furthermore, research suggests that the level of work impairment among cancer caregivers is greater than among the general population [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An analysis of written responses, provided by the 21.2% of survivors who reported that their caregivers made “other” work changes, revealed that caregivers made a broad array of changes to their schedules, job responsibilities and in some cases their careers in order to transport the survivor to and from their medical appointments and provide care during recovery. These findings are consistent with previous research reporting that cancer caregivers miss work, work fewer hours, or make career changes as a result of their caregiving responsibilities [13, 12, 14, 24, 15]. Furthermore, research suggests that the level of work impairment among cancer caregivers is greater than among the general population [25].…”
Section: Discussionsupporting
confidence: 90%
“…A range of issues have been reported by informal cancer caregivers, including psychosocial and emotional problems, physical health problems, and decreased quality of life [5, 11, 9, 12]. For individuals who are employed, the time spent providing care can impel caregivers to take time off from work, which can lead to lost wages and financial hardship [12-15]. …”
Section: Introductionmentioning
confidence: 99%
“…Out‐of‐pocket expenses due to travel, accommodation, childcare, food, gifts, and treats were identified as significant sources of financial burden . Work disruptions as a result of a child's treatment were ubiquitously reported, including at least one parent quitting a job to provide care for their child in 30–50% of families . Variations in study design—including duration of follow‐up and included costs—make precise reporting of the magnitude of financial costs to families challenging.…”
Section: Resultsmentioning
confidence: 99%
“…4 Caregivers often experience physical stress, negative emotion, economic burden, and undesirable behavioural and physiological impacts. [4][5][6][7][8] The enormous burden reduces the caregivers' quality of life, which may reduce their ability to take care of the cancer patients. 9,10 Due to the limited cognitive ability of the children with ALL, family caregivers, particularly the parents, play an important role in delivering complex health care services in and out of the hospital.…”
Section: Introductionmentioning
confidence: 99%